Characteristics of Desalination Brine and Its Impacts on Marine Chemistry and Health, With Emphasis on the Persian/Arabian Gulf: A Review - Omerspahic, Mustafa; Al-Jabri, Hareb; Siddiqui, Simil Amir; Saadaoui, Imen (Frontiers in Marine Science, 2022)
At a time when worldwide water shortage is increasing, seawater is being viewed as an inexhaustible supply of fresh water via the process of seawater desalination. As a result, seawater desalination is becoming more popular, especially in areas where fresh water is scarce, such as the Middle East and North Africa (MENA), which accounts for half of all global saltwater desalination activities. To enhance the efficiency of saltwater desalination, thermal and membrane-based desalination technologies are continually being developed and hybridized systems are established. Brine is an unavoidable product of seawater desalination and is commonly disposed of in oceans and seas, where it has negative effects on the surrounding marine environment and its biodiversity due to the resultant increased salinity and temperature, as well as the presence of chemicals. Furthermore, the quality and amount of brine are influenced by several parameters, including the input quality and quantity, the desalination process, and the discharge method. The intensity of brine's influence on the marine biota is determined by a number of factors; nevertheless, marine species differ in their tolerance to brine's effects. Desalination technology is improving to maximize water recovery and reduce the volume of brine produced, with the objective of eventually reaching zero liquid discharge and limiting harmful effects on the marine environment. Meanwhile, proper systems for analyzing the effects of seawater desalination facilities on the marine ecology must be implemented. This review study will look at all of the factors that determine the physicochemical features of desalination brine, with a focus on its impact on marine chemistry and biodiversity. More crucially, the most cutting-edge brine management methods will be investigated for long-term desalination and a healthy marine ecosystem.